Color–tunable luminescence and energy transfer behaviors of Dy3+/Eu3+ co–doped SrLaMgTaO6 phosphors for solid state lighting applications. (April 2017) - Guo, Yue; Moon, Byung Kee; Choi, Byung Chun; Jeong, Jung Hyun; Kim, Jung Hwan
Graphical abstract: Highlights: Excited by 354 nm, the samples showed TaO6 group, Dy 3+ and Eu 3+ ions emission. The band gap was calculated by VASP and diffuse reflectance spectra. The ET mechanism from Dy 3+ to Eu 3+ ions are the exchange interaction. The integral intensity kept about 83.34% at 150 °C of that measured at 30 °C. The warm and cold white light emission could be generated. Abstract: A series of color–tunable SrLa0.93-y MgTaO6 :0.07Dy 3+, yEu 3+ phosphors were synthesized via solid–state reaction. The X–ray diffraction, diffuse reflectance spectra, luminescent spectra, lifetimes and thermal quenching were applied to characterize the obtained phosphors. The X–ray diffraction results revealed that the obtained phosphors possessed pure monoclinic phase. The band gap of SrLaMgTaO6 was calculated from Vienna ab initio simulation package and diffuse reflectance spectra. The energy transfers from host to Dy 3+ and Eu 3+ ions were confirmed by the luminescence spectra. Furthermore, the SrLa0.92 MgTaO6 : 0.07Dy 3+, 0.01Eu 3+ phosphor had excellent thermal stability, while the integrated PL intensity still kept about 83.34% at 150 °C of that measured at room temperature (30 °C). In addition, the warm and cold white light emission could be generated with different Eu 3+ contents. All the results of SrLa0.93-y MgTaO6 :0.07Dy 3+, yEu 3+ phosphors show great potential as a single–phase white–emitting phosphor for solid state lighting applications.